UV-VIS and photoluminescence spectroscopy for nanomaterials characterization - Kumar, Challa (Springer Berlin Heidelberg, 2013)
Second volume of a 40-volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about UV-visible and photoluminescence spectroscopy for the characterization of nanomaterials. Modern applications and state-of-the-art techniques are covered and make this volume essential reading for research scientists in academia and industry in the related fields.